Maternal and fetal outcomes in non-obstetric surgery and anesthesia during pregnancy: A retrospective analysis of data in a territory university hospital (Annals of Medical Research, 2023)
Aim: We aimed to evaluate the maternal effect of anesthesia in patients who underwent non-obstetric surgery during pregnancy. Our secondary aim was to investigate the fetal effects of anesthesia including time of birth and the newborn characteristics.Materials and Methods: Patient data was obtained through the hospital information management system and anesthesia records. Records of the patients between January 1, 2017 and December 31, 2021 were reviewed. Pregnant patients who underwent a non-pregnancy surgical intervention were included in the study. Demographic characteristics of the patients, gestation week, anesthesia methods, anesthesia management, fetal and maternal complications were recorded. Neonates were assessed in the postoperative period using APGAR score.Results: Records of 75 patients were included in the study 12 patients were excluded due to cesarean section or fetal operation in the same session. Sixty-three patients were analyzed. The mean age was 27.75±5.31 years. The mean gestational week was 17.79±8.07 weeks. 24 of the patients were operated in the 1st trimester, 29 were in the 2nd trimester, and 10 were in the 3rd trimester. General anesthesia was administered in 39 patients. Spinal block was implemented in 24 patients. We observed one fetal loss, the frequency of abortus was calculated as 1.58 %. The 1st and 5th minute APGAR score averages of babies born in our hospital were 8.75±0.64 and 9.78±0.62, respectively.Conclusion: General and regional anesthesia techniques can be considered safe in patients undergoing non-pregnancy surgery. Newborn appear to be in good health, even if they are born prematurely. Although conducting large-scale randomized controlled studies in pregnant patients is not possible due to ethical considerations, further prospective observational studies are needed.